ENGLISH GRAMMAR MASTERY OF THE FIRST SEMESTER STUDENTS - Wersi Murtini Ni Made (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2021)
The aspects of English tenses enable to show the time and its relation to the activities or events in spoken or written language (Stern, 2002:42). This study focused on assessing the ability of the first semester students in tenses mastery. The samples were 28 students from the first semester of Class B of English Language Education Study Program, FKIP Unmas Denpasar. The subjects of this study were determined by using cluster sampling method. The data were collected by administering multiple choice test instrument which were analysed using a norm-referenced measure of five standard values. It showed that (1) there is only 1 subject (3.57%) showed excellent ability in mastering grammar, (2) there are 9 subjects (32.14%) showed good ability, (3) there are 11 subjects (39.27%) showed sufficient ability, (4) there are 4 subjects (14.28%) showed insufficient ability, and (5) there are 3 subjects (10.74%) showed poor ability in mastering grammar. There are 7 students (25.02%) out of 28 students who failed in learning and acquiring English grammar. It means that 25.02% of them still have low ability. In this case the students should be given more chances and exercises to be active in the teaching and learning processes.